HUBUNGAN ANTARA ISLAM DAN PSIKOLOGI: PENDEKATAN MULTIDISIPLINER DALAM MEMAHAMI KESEHATAN MENTAL MUSLIM - Rijali, Syaddam; Telaumbanua, Dewi Angreini; Pane, Derliana (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The interconnection between Islam and psychology is an area that is currently receiving attention in multidisciplinary studies, especially in understanding the mental health of Muslim communities. This paper examines the interaction between Islamic religious teachings and psychological principles in the context of mental health by emphasizing a holistic approach that includes spiritual, emotional, and social aspects. Islamic teachings offer a strong life guide including how to manage stress, anxiety and other psychological problems through worship activities, prayer and strengthening social bonds in the community, especially the Muslim community. On the other hand, modern psychology provides a framework for understanding and treating mental disorders scientifically, but often ignores the spiritual dimension of the healing process. By integrating religion and psychology, it can support psychological therapy and improve the mental well-being of the Muslim community. This multidisciplinary approach can offer a more comprehensive alternative in supporting Muslim individuals in dealing with mental health challenges that are aligned with their religious teachings and spiritual practices.